ANALISIS KEUNTUNGAN NILAI TAMBAH AGROINDUSTRI SIRUP PALA PADA CV. NOVITA DI DESA KAREGESAN KABUPATEN MINAHASA UTARA (Profit Analysis of the added value obtained from processing the nutmeg syrup at CV. NOVITA in Karegesan Village, North Minahasa Regency) - Kaseretang Mareyke Monica; Caroline B. D. Pakasi; Celcius Talumingan (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
The purpose of this study was to calculate the added value obtained from processing the nutmeg syrup at CV. NOVITA. This research was conducted in Karegesan village, North Minahasa district. This research was conducted for 3 months from September to November 2019. The data used in this study were primary data. CV. Novita produces three times a month. Based on the research results, it could be concluded that the nutmeg syrup business at CV. NOVITA in Karegesan village, North Minahasa Regency was very profitable and had an added value from the nutmeg pulp into nutmeg syrup of Rp. 4,621,000. This means that this industry is feasible to develop.